The Influence of Discipline and Workload on Work Effectiveness through Organizational Support among Lecturers at the State Islamic Institute (IAIN) Parepare - Niswahilma; Muh. Akob; Syamsul Alam (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the influence of discipline and workload on work effectiveness through organizational support. The subjects in this study were 80 lecturers at the State Islamic Institute (IAIN) Parepare. The research method used in this study is a quantitative method. The data analysis technique used is partial regression analysis using SmartPLS 4. The findings in this study indicate that the discipline variable has a negative and insignificant effect on organizational support. Discipline has a positive and significant effect on work effectiveness. Workload has a positive and significant effect on organizational support. Workload has a positive and significant effect on work effectiveness. Organizational support has a positive and insignificant effect on work effectiveness. Discipline, when mediated by organizational support, shows a very weak and statistically insignificant negative impact on work effectiveness. Workload through organizational support shows a positive and statistically insignificant impact on work effectiveness.